Evaluasi Pengelolaaan Kawasan Agropolitan Pakakaan Kabupaten Minahasa Selama Masa Pandemi Covid-19 - Tendean, Mario Fernando; Katiandagho, Theodora Maulina; Kapantow, Gene H.M. (Sam Ratulangi University, 2023)
This study aims to evaluate the management of Pakakaan Agropolitan Area, Minahasa Regency. This research was conducted in the Pakakaan Agropolitan Area, Minahasa Regency from July to August 2022. The data used in this research are primary and secondary data. Primary data were obtained through interviews with the head of BAPPEDA, the Public Works Office, the Minahasa Regency Agriculture Office and observation. Secondary data obtained from the Minahasa Central Bureau of Statistics. The variables measured in this study are superior commodities and supporting facilities and infrastructure. The data analysis method used is descriptive analysis. The results showed that the total production of leading commodities in the Pakakaan Agropolitan Area continued to increase even during the Covid-19 pandemic, and the Pakakaan Agropolitan Area had infrastructure facilities that could support agriculture, there was a network of connecting roads between villages, cities, business roads for farmers and there was a network irrigation but the management and maintenance did not go well due to the Covid-19 pandemic which caused a diversion of the budget to the Health Service.